2018
DOI: 10.1208/s12249-018-1140-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Simulated Fasted Gastrointestinal pH Profiles on Diclofenac Sodium Dissolution in a Glass-Bead Flow-Through System

Abstract: High inter- and intra-individual variability in the pH of fluids in the human gastrointestinal (GI) tract has been described in the literature. The aim of this study was to assess the influence of physiological variability in fasted pH profiles of media along the GI tract on diclofenac sodium (DF-Na) dissolution from matrix tablets. Four individual in vivo fasted pH profiles were selected from the literature that differed in pH values and transit times from the stomach to the proximal colon. Using a glass-bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The first layer was composed of RhB and C1 dextran ester while the second and third layers consisted in MB/SC2 and Nap/SC4 nanofibers, respectively. In vitro release studies were performed in simulated gastrointestinal pH and transit times, based on reported in vivo measurements , (see Figure ). In simulated stomach condition, the pH value was 3.5 for 15 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first layer was composed of RhB and C1 dextran ester while the second and third layers consisted in MB/SC2 and Nap/SC4 nanofibers, respectively. In vitro release studies were performed in simulated gastrointestinal pH and transit times, based on reported in vivo measurements , (see Figure ). In simulated stomach condition, the pH value was 3.5 for 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…The stimuli-responsive properties and hierarchical structure of the material are designed to match temporal and pH conditions encountered in the gastrointestinal tract. 41,42 ■ EXPERIMENTAL SECTION Materials. Dextran (M r = 70 000 g mol −1 , Sigma-Aldrich), succinic anhydride (99%, Acros Organics), 1,2-cyclohexanedicarboxylic anhydride (95%, Sigma-Aldrich) lithium chloride anhydrous (LiCl) (>98%, TCI), N,N-dimethylformamide (DMF) (99.9%, Carlo Erba), dichloromethane (DCM) (99.9%, Honeywell), methanol (99.99%, Honeywell), rhodamine B (RhB, > 90%, Merck), monosodium phosphate (98%, Carlo Erba), sodium hydroxide (NaOH) (98%, Carlo Erba), hydrochloric acid (HCl) (37%, Carlo Erba), triethylamine (99%, Merck), 4-bromo-1,8-naphthalic anhydride (>95.0%, TCI), β-alanine (99%, Acros Organics), acetone (99.5%, Carlo Erba), and Eudragit L 100−55 (97.0%, Evonik) were used as received.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the integrated biopharmaceutical approach in pharmaceutical development and drug characterization, dissolution testing is expected to serve as a substitute for in vivo testing, and the focus is placed on the discriminatory in vivo predictive dissolution test development and establishment of clinically relevant dissolution specifications [10][11][12]. While the most often used dissolution equipment for oral dosage form characterization includes compendial rotating paddle/rotating basket apparatus, extensive research efforts are directed towards design of dynamic apparatus which would more closely mimic hydrodynamics and transit times encountered in vivo, including the use of complex media, which simulate composition of physiological fluids in different parts of the gastrointestinal tract [13][14][15][16]. Two distinct approaches have been recognized: (i) biorelevant dissolution method which attempts to mimic complex factors, which are encountered under the physiological conditions in vivo, and may be useful in guiding formulation development and identification of food effects, and (ii) in vivo predictive (or, biopredictive) dissolution (iPD) method which includes a set of testing conditions that enable prediction of relevant pharmacokinetic profile, and is typically based on the established IVIVC [17].…”
Section: In Vivo Predictive Dissolution Testingmentioning
confidence: 99%
“…For some dosage forms, particularly for those with pH-dependent drug release, these variabilities can be the source of BA issues. The study on assessing the impact of physiological variability in fasted GI pH profiles on diclofenac sodium release from matrix tablets ("The Influence of Simulated Fasted Gastrointestinal pH Profiles on Diclofenac Sodium Dissolution in a Glass-Bead Flow-Through System") represents an attempt for estimating in vivo drug release of a weakly acidic drug compound from an ER formulation in individual subjects (7) and is a simple precursor method of more advanced individualized in vitro methods that target on a precise prediction of the in vivo performance or an in vitro-in vivo correlation (IVIVC), respectively (8,9).…”
mentioning
confidence: 99%